A synopsis of the cytogenetics of the genus Phlomoides (Lamiaceae) in Iran. Issue 4 (1st October 2016) - Ranjbar, Massoud; Mahmoudi, Chonour; Jahaniyan, Sepideh
Abstract: The present study reports the chromosome number and meiotic behavior of 11 populations belonging to four species of Phlomoides (L.) Moench. All populations showed the diploid chromosome number 2 n  = 2 x  = 22; consistent with the proposed base number of x  = 11. Almost all taxa studied here displayed regular bivalent pairing and chromosome segregation at meiosis. However, meiotic abnormalities observed included varied degree of fragmented chromosomes, laggards and bridge in anaphase I to telophase II, precocious division of centromeres, asynchronous nucleus and cytomixis. In addition, a survey on chromosome counts of different species belonging to the genus Phlomoides throughout the world is presented and the base chromosome numbers and polyploidy levels discussed here.